2021
DOI: 10.4081/monaldi.2021.1915
|View full text |Cite
|
Sign up to set email alerts
|

Single coronary artery originating from right sinus. Role of MDCT and a review of literature

Abstract: SCA from the right sinus is the rarest coronary anomaly. We describe 2 cases: 1 with SCA type-1RI; 2 with SCA type-2RII-A. Appropriate and successful treatment (CABG in case-1; PTCA in case-2) was chosen relying on accurate morphological description provided by MDCT, in order to recognize all the possible mechanisms of myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…It is unusual for a single coronary artery to originate from the right coronary sinus. Similar cases were described by Özyurtlu et al and Pergola et al, and studies show that they comprised 3.3% of all coronary anomalies [27,28].…”
Section: Discussionsupporting
confidence: 85%
“…It is unusual for a single coronary artery to originate from the right coronary sinus. Similar cases were described by Özyurtlu et al and Pergola et al, and studies show that they comprised 3.3% of all coronary anomalies [27,28].…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, the gothic aortic arch anomaly can influence ventricular–vascular interactions, particularly regarding ventricular load and contractility. [ 7 ] These changes may be related to the LVNC trigger as a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Desmet et al [ 24 ] reported that the first case of single coronary artery was described in 1716 by Thebesius. About 45 cases of single coronary artery had been documented until 1950 [ 26 ]. In 1979, it was presented very useful classification of anomalies which includes single coronary arteries [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pergola et al described two similar cases. Both patients reported epigastric pain with nausea, vomiting, vertigo, and weakness [ 26 ].…”
Section: Discussionmentioning
confidence: 99%